Neurociência e os processos cognitivos: práticas pedagógica e perspectivas da aprendizagem no ensino de ciências nos anos iniciais - Navegante, Polyana Milena Barros (2016)
This study is focused on a Neuroscience and Cognitive Processes, and aims to analyze how neuroscience contributions in relation to cognitive processes, que facilitate as pedagogical practices of teachers and learning in Science Teaching. It is known que teachers need to establish connections with OS brain CONTENT, Scientific and Technological Knowledge, searching YOUR Continuing Education initial UO, Understanding, acquisition and use of neuroscience Fundamentals que possible to develop skills, skills to motivate, teach with innovative strategies , reflective, able to facilitate the best possible way to optimize learning. We opted As a descriptive study of exploratory nature essentially qualitative. For Obtaining Data were held Bibliographical Research, participant observation, talk, Questionnaires and applicability of workshops with neuroscientific approaches. The sample consisted of 17 professors, 01 managers and 01 pedagogue of a municipal public school que submitted proposed AOS resources, allowed to answer the research objectives. Among OS Various Authors What underlie this study include: Relvas (2000, 2012), Resende (2008), Oliveira (2011), Cosenza (2011), Metring (2011) and Morin (2005) and War (2010), Vigotsky (2007) Piaget (2007), Ausubel (1978), Freire (2001). The results showed the need for paragraph Teachers use a Cognitive Neuroscience How paragraph contribution as strengthen their teaching practices